Legal Challenges to the Protection of the Serbian Orthodox Church’s Property Rights in Kosovo and Metohija: The Case of the Visoki Dečani Monastery - Kabašić, Danica N. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The specific political and legal circumstances in Kosovo and Metohija after 1999 have seriously restricted and jeopardized the property rights of the Serbian Orthodox Church, particularly with regard to immovable property of special spiritual, cultural, and historical significance. In practice, the exercise of these rights has often been limited by institutional obstruction, selective application of regulations, and the absence of effective mechanisms for enforcing final court decisions. As a result, ownership has existed only formally, without full legal protection or the effective enjoyment of the rights attached to it. As a case study, the paper analyzes the legal dispute concerning the registration of Visoki Dečani Monastery’s ownership rights over 24 hectares of land in the real estate cadastre, despite the existence of valid legal documentation and final court rulings. The dispute lasted for more than twenty years and was not resolved until 2024, outside the framework of regular institutional action and within the broader context of the international assessment of the rule of law situation. Using legal-dogmatic analysis, a case study approach, and the analysis of judicial practice, and drawing on relevant legal acts, court decisions, official sources, and field materials, including access to documentation and communications with participants in the proceedings, the paper examines the legal nature and consequences of the long-term non-enforcement of a court decision. The findings indicate that such conduct may be regarded as a violation of the right to a fair trial and the right to the peaceful enjoyment of possessions, as well as a form of interference with property rights which, by its effects, corresponds to the concept of de facto expropriation, given that the owner was prevented from effectively exercising that right. The paper concludes that the absence of an effective mechanism for the enforcement of court decisions represents one of the key challenges to the rule of law, calling into question the very essence of formally guaranteed property rights.
Keywords: Visoki Dečani Monastery; Serbian Orthodox Church; Kosovo and Metohija; restrictions on property rights; right to the peaceful enjoyment of possessions; deed of gift